Analysis of the Utilization of Artificial Intelligence in Shopee's Live Feature Based on Competition Law - Jaudah, Tsuroyyaa Maitsaa; Fadil Muhammad; Garni Sriwangi; Princess Alyssa D. Tee-Anastacio (Journal of Private and Commercial Law, 2024)
The rapid development of technology has had a significant impact on various aspects of life, one of which is the economic sector. The application of technology in the economic sector involves the use of AI in e-commerce, particularly in the live feature of Shopee, which provides substantial benefits for business actors. However, it can also create imbalances in the market at times. The market imbalance has led to unhealthy business competition practices that are contrary to Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. The purpose of this research is to analyze the utilization of AI in Shopee's live feature, which is indicated to potentially lead to unfair business competition practices based on Competition Law. The method used in this research is normative empirical, combining the implementation of positive law with legal events occurring in society. The utilization of AI in Shopee's live feature causes an imbalance in the market by providing significant advantages to business players who possess multiple AI models, allowing them to dominate up to 50% of the market share for certain products and hindering new competitors from entering the market. The use of AI in Shopee's live feature leads to market dominance and a dominant position by business players, which contradicts Articles 19 and 25 of Law Number 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition.